A new flexible geothermal based cogeneration system producing power and refrigeration, part two: The influence of ambient temperature. (April 2019) - Akbari Kordlar, M.; Mahmoudi, S.M.S.; Talati, F.; Yari, M.; Mosaffa, A.H.
Abstract: A novel combined cooling/power cogeneration system, including a modified Kalina cycle and an absorption refrigeration cycle is proposed. The cycle uses ammonia-water as working fluid and is driven by geothermal energy. The cycle is flexible for producing different ratios of power to cooling capacities. It is observed that the ambient temperature and the split mass flow ratio at the condenser exit play major roles on the system performance. The results show that in summer time a better economic performance and also a higher cooling to power ratio is achieved. It is also seen that the overall system exergy efficiency is maximized at a specific value of the split mass flow ratio and that the total product unit cost is minimized at some specific values of the generator temperature and split mass flow ratio. The system performance is optimized considering the exergy efficiency and total product unit cost as criteria. The optimization results show that when the criterion is selected as exergy efficiency, a better economic performance is also achieved for the system. It is found that the highest exergy efficiency of the system is achieved as 33.61% and the lowest total product unit cost is obtained as 39.93/GJ. Highlights: A novel combined cooling and power cogeneration system is proposed. Exergeoconomic analyses are performed in different seasons. Exergy efficiency is maximized and unit cost is minimized at different seasons. Effects on system performance is investigated of key parameters in proposed cycle. Higher condenser temperature is in favor of cooling and against power outputs.